2014
DOI: 10.1039/c4ra09472g
|View full text |Cite
|
Sign up to set email alerts
|

Stability of ruthenium/organic dye co-sensitized solar cells: a joint experimental and computational investigation

Abstract: A joint experimental and theoretical study on the stability of dye-sensitized Solar Cells employing a mixture of black dye (N749) and Y1 organic coadsorbent is presented. The aim of the present work is to investigate the stability of these sensitizers, representing the efficiency state of the art in this field. Under the investigated conditions (1100h of ~1Sun light soaking at 55˚C) the co-sensitized device has shown a remarkable stability. The partial desorption of the organic co-adsorbent has been individuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 76 publications
(141 reference statements)
0
14
0
Order By: Relevance
“…It is important to note about the three important properties which are dependent on the anchoring group moieties. These properties include (a) electronic coupling between the dye and metal oxide photoanode, (b) orientation and packing of the adsorbed dye molecules and (c) long-term stability of the device [214,215]. Besides, the available anchoring site for the dye 2 depends upon the surface area of the TiO 2 nanoparticles.…”
Section: Methods and Methodologies Of Co-sensitizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note about the three important properties which are dependent on the anchoring group moieties. These properties include (a) electronic coupling between the dye and metal oxide photoanode, (b) orientation and packing of the adsorbed dye molecules and (c) long-term stability of the device [214,215]. Besides, the available anchoring site for the dye 2 depends upon the surface area of the TiO 2 nanoparticles.…”
Section: Methods and Methodologies Of Co-sensitizationmentioning
confidence: 99%
“…For instance, it has been experimentally found that the binding of benzoic acid takes place through bidentate mode whereas for cyanoacrylic acid it's a tridentate mode [254]. These kind of different mode attachment of dyes also influenced by their geometrical parameters [214,215]. Each dye has some specific adsorption sites on the surface of the photoelectrode and hence there will be some available sites for the second dye adsorption.…”
Section: Methods and Methodologies Of Co-sensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The IPCE spectrum of black dye+Y1 displayed broad absorption at wavelengths from 300 to 700 nm, leading to enhanced J SC of 20.88 mA cm −2 , whereas black dye+Y2 absorbed only in a narrow range of wavelengths from 350 to 420 nm. Thus, the PCE of black dye+Y1 improved up to 11.3 % when compared with the efficiency of black dye+Y2 . Additionally, the D–π–A architecture of Y3 co‐sensitized with ampiphilic Ru‐based dye (Amp Ru, Figure ) aids to reduce dye aggregation, charge recombination, and back‐electron transfer, thereby enhancing PCE (CR2 mechanism) .…”
Section: Charge Recombination Processesmentioning
confidence: 99%
“…Thus, the PCE of black dye + Y1 improved up to 11.3 %when compared with the efficiencyo fb lack dye + Y2. [51] Additionally,t he D-p-A architecture of Y3 co-sensitized with ampiphilic Ru-based dye (Amp Ru, Figure 2) aids to reduce dye aggregation, charge recombination, and back-electron transfer,t hereby enhancingP CE (CR2 mechanism). [52] The IPCE of Amp Ru + Y3 showeda bsorption band covering 300-800 nm, reaching am aximum of 80 %.…”
Section: Effect Of Co-sensitizersi Nrum Etal Complexesmentioning
confidence: 99%